Morpho-histological Study of the Rat Spleen Post-Induction of Sodium Nitrite and Acorus calamus L. Rhizome Ethanolic Extract - Amira, Siti; Febriani, Husnarika; Syukriah, Syukriah; Nur Faizah, Ulinnuha (Jurnal Riset Biologi dan Aplikasinya, 2023)
Sodium nitrite (NaNO2) is one of the most inorganic salts and is often used in processed meat products. Long-term consumption of sodium nitrite has been reported to cause of oxidative stress and spleen histological changes. Therefore, anti-oxidative effects are needed from natural ingredients such as Acorus calamus L. The study aims to determine the effect of A.calamus L. rhizome extract on anatomical structure and histological changes in the rat spleen induced with NaNO2. We used a completely randomized design with twenty-five male rats divided into 5 groups. Negative control (NC) was given 0.5% CMC for 40 days; positive control (PC) on days 1-15 was given NaNO2 (50 mg/kg BW); on days 16-30 given (50 mg/kg BW) NaNO2 + 0.5% CMC and on days 31-40 given 0,5% carboxy methyl cellulose (CMC). Treatment 1 (T1), Treatment 2 (T2), and Treatment 3 (T3) on days 1-15 were given NaNO2 doses of 50 mg; and; on days 16-30, groups T1, T2, and T3 were given NaNO2 + extract with each predetermined dose (250 mg/kg BW for T1, 500 mg/kg BW for T2, and 750 mg/kg BW for T3). For days 31-40 groups T1, T2, and T3 were given extracts with each predetermined dose. Results revealed that the extract of the A. calamus L. rhizome affects weight, length, and width of the spleen (P<0.05); and bleeding lesions; while having no noticeable effect (P<0.05) and having a noticeable effect on the area of the white pulp (P<0.05). Administration of ethanol extract of A. calamus L. at a dose of 250 mg/kg BW has an impact on improving spleen length; a dose of 500 mg/kg BW has an impact on the weight and length of the spleen; and a dose of 750 mg / kg BW has an impact on improving spleen length, but the size variation is still in the normal category. While extracts at doses of 250 and 500 mg/kg BW have a repair impact on tissue shrinkage in damaged white pulp.